Nutritional Counseling On Energy, Protein, Vitamin C And Iron Intake. - halil munawir; Mustamin Mustamin; Ramlan Asbar (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Chronic energy deficiency is one of the nutritional problems of pregnant women where the body's condition experiences a severe lack of energy or is often showed by upper arm circumference <23.5. chronic energy deficiency of pregnant woman caused by many factors. one of the factors is low intake of nutrients such as energy, protein, vitamin c and iron. This study aims to determine the effect of nutritional counseling on energy, protein, vitamin c and iron intake. This type of research is a quasi experiment analytic research using cross sectional research design. sample was 30 pregnant women. extension data based on extension program unit then narrated nutrient intake obtained through 4X24 hour recall. the results of the study showed that before the extension of the sample energy intake was 96.7% less and 3.3% more. Sample protein intake as much as 100% less. Intake of vitamin C sample as much as 100% less. Sample iron intake is as much as 100% less. after counseling of sample energy intake as much as 3,3% good and 96,7% less. Sample protein intake as much as 100% less. Vitamin C intake was 3.3% good and 9.3% less and 6.7% more. Sample iron intake is as much as 100% less. Average intake before and after counseling of nutrients classified as less. It is recommended to increase nutrient intake. should be done further research on other factors that affect.